PERANCANGAN APLIKASI INFORMASI BENGKEL MOBIL DAERAH JAKARTA BARAT BERBASIS ANDROID - Rizky Muhammad Usup; susafaati susafaati (University of Muhammadiyah Tangerang, 2021)
The vehicel describe wrong one tool transportation that most needed as a means transportation in activity daily. Driver or riders normally have desire while driving i.e comfort in driving. driver could get comfort in driving with service vehicle an routine. car workshop is a place to fix vehicle that broke down or do service an rutin. author aims designing application this to assist driver get information abbout car workshop nearby and prevent occurrence accident result rarely do service vehicle car. Method algorithm that used in designing application this i.e use method algorithm djikstra. Algorithm Dijkstra is algorithm determine distance shortest from point A to point B. Application this also use google maps as map that could ease users to location car workshop that headed. With availabity application is be expected can help and facilitate consumer within doing activity in Jakarta Barat, if having problems vehicle to heave. Keywords : Djikstra, Car Workshop, Android